The Effect of Mathematical Ability and Mental Habits on Academic Achievement in Mathematics - مطر اماني محمد; كاظم رشا مالك; وشيل رسل محسن (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The current study aimed to assess the effectiveness of mathematical ability and mental habits on students’ academic performance in mathematics. Mathematical ability refers to students’ capacity to understand and grasp mathematical concepts, symbols, their application, and recall. Mental habits are the habits that assist in organizing and structuring mental processes, establishing a sound priority system for these habits, due to their significance in enhancing human intelligence.